To the farm, Mars, and beyond: Technologies for growing food in space, the future of long-duration space missions, and earth implications in English news media coverage - Shaw, Ryland; Soma, Tammara (Frontiers in Communication, 2022)
The climate crisis, natural resource exploitation, and concerns around how to feed a growing world population have resulted in a growing chorus identifying the need for a Plan B. For some, this Plan B entails preparing for long-duration space missions and the development of human settlement on Mars. To plan for long-duration space missions, the development of food production technologies that can withstand extreme conditions such as poor soil, lack of gravity, and radiation are increasingly prioritized. These technologies may include genetic engineering, digital agriculture, 3D bioprinting, synthetically grown meat and more. Government and corporate proponents of long-duration space missions—NASA and SpaceX, among others—are actively funding agricultural research in space. They argue that the technologies developed for space will have positive implications beyond Mars—directly benefitting Earth and its inhabitants. This paper demonstrates that news reporting on the technology has been overall uncritical. Media narratives surrounding issues of food growth in space have not been studied. This study analyzes how English news media coverage (n=170) from 67 publications report the feasibility of long-duration space missions, human settlements, and high-tech agricultural technologies. We provide a cross-section of the types of agricultural technologies being covered, the key organizations and actors in the field, and a critical analysis of media narratives. Using mixed methods content and discourse analysis, this study finds that the news media publications overwhelmingly portray long-duration space missions as both inevitable and a positive good for humanity. Without critically assessing the societal implications of food technologies for long-duration space missions vis-à-vis their benefits on Earth, we risk glossing over systemic and structural inequalities in the food system.